A practical method for computing the thermal properties of a Ground Heat Exchanger - Christodoulides, Paul; Florides, Georgios A.; Pouloupatis, Panayiotis (My University, 2016)
The aim of this paper is to show a practical way of estimating the thermal ground properties, namely the ground thermal conductivity, and in particular the thermal diffusivity and the volumetric heat capacity in a reliable manner, for sizing Ground Heat Exchangers (GHEs). A well-known thermal model, proposed by Blackwell in 1954, is applied and is validated both in the heating mode and in the cooling mode, using a GHE as a probe. The value of the thermal conductivity can be easily determined by the model but the procedure also requires knowledge of the ground specific heat capacity and density, which are normally deduced from the (non-accurate) geological data of the site. In addition to the above, the thermal model is also solved analytically –based on the actual parameters used in the experiment–leading to the computation of the ground thermal diffusivity, the volumetric heat capacity and the thermal resistance of the GHE. The possible errors and drawbacks of the whole method are then discussed and finally a complete set of guidelines is provided to the field Engineer for estimating the ground thermal properties from a single test, rendering the use of the geological data of the side unnecessary.
Keywords: Ground thermal properties; Line-source method; Ground heat exchanger; Borehole; Thermal characteristics